Development of E-Modules Assisted by Geogebra Software to Improve High School Students' Mathematical Problem Solving Abilities - Sihombing, Betrik; Purba, Glory Indira D. (Jurnal Pendidikan Matematika, 2025)
This research is motivated by students' low mathematical problem solving abilities in  mathematics learning process, which includes four indicators, namely understanding the problem, making a plan, implementation the plan and looking back. The aim of this research is to develop an e-module assisted by geogebra software to improve students' mathematical problem solving abilities. The method used is development research with ADDIE model, analysis, design, development, implementation and evaluation. Data collection techniques used are observation, interviews, questionnaires and tests. The research results show that e-module assisted by geogebra software developed on quadratic function material is suitable use for teaching material that can improve students' mathematical problem solving abilities. This is based on media and material expert validation results of 93% (very valid category), teacher practicality results of 88% and student practicality results of 94% (very practical category), student classical learning completion results of 97% (very effective category) which can achieving complete achievement of learning objectives, the results of student effectiveness questionnaire response to the e-module of 98% (very effective category). It can be concluded that e-module assisted by geogebra software developed on quadratic function material meets the criteria for validity, practicality and effectiveness, so it can be used to improve students' mathematical problem solving abilities.